2022
DOI: 10.1159/000524996
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Lung Volume Reduction with One-Way Valves in Patients with Severe Chronic Obstructive Pulmonary Disease with Hypercapnia

Abstract: <b><i>Background:</i></b> Robust clinical evidence on the efficacy and safety of endoscopic lung volume reduction (ELVR) with one-way valves in patients with severe lung emphysema with chronic hypercapnic respiratory failure is lacking. <b><i>Objective:</i></b> The aim of this study was to compare patient characteristics, clinical outcome measures, and incidences of adverse events between patients with severe COPD undergoing ELVR with one-way valves and with eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Remarkably, arterial blood gas analysis at follow-up showed that 40% of the patients had a normalized pCO 2 , probably due to improved respiratory mechanics effectuated by the reduction in hyperinflation. These conclusions were also supported in a multicentre trial by Lenga et al 14 ,. showing a greater reduction in pCO 2 after valve placement in patients who were more hypercapnic at baseline when compared to normocapnic patients.…”
Section: Advances In Patient Selectionsupporting
confidence: 63%
“…Remarkably, arterial blood gas analysis at follow-up showed that 40% of the patients had a normalized pCO 2 , probably due to improved respiratory mechanics effectuated by the reduction in hyperinflation. These conclusions were also supported in a multicentre trial by Lenga et al 14 ,. showing a greater reduction in pCO 2 after valve placement in patients who were more hypercapnic at baseline when compared to normocapnic patients.…”
Section: Advances In Patient Selectionsupporting
confidence: 63%
“…This is consistent with previous publications that showed that patients with baseline measures below (previously) recommended selection criteria (such as residual volume ≤175% pred [ 23 ] or FEV 1 ≤20% pred [ 24 , 25 ]) can also significantly benefit from EBV treatment [ 5 ]. Furthermore, EBV treatment was found to be safe and clinically beneficial in patients with a lower level of D LCO (≤20% pred [ 26 , 27 ]) or clinically relevant hypercapnia (partial pressure of carbon dioxide ≥45 mmHg [ 28 , 29 ]). Of course, it would be helpful, especially for pulmonary physicians starting up a lung volume reduction programme at their hospital to have guidance on patient selection and thus clear cut-off values on standard baseline measures such as pulmonary function outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EBV treatment was found to be safe and clinically beneficial, inpatients with a lower level of DLCO (≤20% of predicted) [27,28] or clinical relevant hypercapnia (pCO2≥ 45mm Hg). [29,30] Of course, it would be helpful, especially for pulmonary physicians starting up a lung volume reduction programme at their hospital to have guidance on patient selection and thus clear cut-off values on standard baseline measures such as pulmonary function outcomes. However, our results, together with these previous publications suggest that using strict selection criteria might lead to undertreatment of potential responders and that it is more important to look at the bigger picture in which the 'quality' of the target lobe plays a critical role.…”
Section: Discussionmentioning
confidence: 99%